2018
DOI: 10.1016/j.radi.2018.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Is a nurse consultant impact toolkit relevant and transferrable to the radiography profession? An evaluation project

Abstract: The impact toolkit could help assess individual and collaborat ive role impact at a local and national level. The framework provides consultant radiographers with an opportunity to understand and highlight the contribution their roles have on patients, staff, their organisation and the wider profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The evidence of impact of advanced and consultant radiographer roles on patient outcomes is limited (Hardy et al 2016), exacerbated by the unique nature of roles and the focus on clinical delivery. Demonstrating the value of imaging, and hence specific roles, in patient pathways can be difficult (Snaith et al 2018). As expected, the clinical domain remains the overarching component in the consultant role, but this study has identified the complexity of activities which take place on a weekly, daily, and hourly, basis.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The evidence of impact of advanced and consultant radiographer roles on patient outcomes is limited (Hardy et al 2016), exacerbated by the unique nature of roles and the focus on clinical delivery. Demonstrating the value of imaging, and hence specific roles, in patient pathways can be difficult (Snaith et al 2018). As expected, the clinical domain remains the overarching component in the consultant role, but this study has identified the complexity of activities which take place on a weekly, daily, and hourly, basis.…”
Section: Discussionmentioning
confidence: 92%
“…These posts are relatively expensive and in the current financial climate there is a need to demonstrate value to patients, referrers, stakeholders, the health system and society (Barrie 2014). Although there have been numerous publications describing the lived experience of the consultant radiographer role from a personal (Jones & Robinson 2008;Kelly et al 2008;Rees 2014), or independent perspective (Ford 2010;Forsyth & Maehle 2010;Hardy & Nightingale 2014a, 2014bBooth et al 2016;, there remains a lack of evidence quantifying the impact of such practice on a day to day basis (Hardy et al 2016;Snaith et al 2018). The activity diaries provide insight into the individual contributions to patient care, staff leadership and service delivery.…”
Section: Discussionmentioning
confidence: 99%
“…moving from a developmental framework as presented here, towards a framework focussed on the evidencing of impact of the consultant role. 29…”
Section: Discussionmentioning
confidence: 99%
“…A focus on expert clinical practice alone will potentially limit impact of the role, and limited evidence of impact, often confined to local case studies with limited methodological rigour, has been cited in nursing literature as a potential barrier to future growth of consultant practice. 28,29 The Society and College of Radiographers (SCoR) has recently issued guidance to support the development of consultant job plans which advise upon the appropriate proportions of clinical and non-clinical sessions to facilitate working across the four domains of practice. 30 Further criticism of the non-medical career framework has highlighted that newly appointed consultant practitioners are often ill-prepared for working at this level.…”
Section: Introductionmentioning
confidence: 99%
“…The time it will take to read literature will definitely be lesser than the time and effort that will be invested into rectifying errors arising from limited knowledge (Pham et al, 2011). Snaith et al, (2018) also asserts that while it is essential for all nurses to create time to search for best practices in their job domain, settings with advanced nurse practice have effective ways of disseminating highest evidence to other groups of nurse professionals. In research conducted by Dalheim et al (2012), it was discovered that skills in evidence-based practice were statistically significantly associated with the sources of information used.…”
Section: Knowledge Of Time and Evidenced Based Carementioning
confidence: 99%